Iodine in Modern Oxidation Catalysis - Finkbeiner, Peter; Nachtsheim, Boris J. (Synthesis, 2013)
This review discusses the origins of iodine-mediated oxidation catalysis and gives a comprehensive overview on this young field of research. The focus is set on oxidative C–X bond-forming reactions starting from two unfunctionalized C–H and X–H bonds. In addition, iodine-mediated oxidative domino reactions will be discussed.1 Introduction2 Why Iodine?3 C–N Bond Formations3.1 Aziridinations3.2 Oxidative Aminations of Heteroarenes3.3 Oxidative Aminations of sp3 C–H Bonds3.4 Oxidative Amidations and Esterifications4 C–O and C–S Bond Formations5 C–C Bond Formations6 Simple Oxidations of Functional Groups7 Oxidative Domino Reactions8 Conclusion
Keywords: iodine; Umpolung; cross-coupling; oxidation; homogeneous catalysis